LEPROSY CARRIER PATIENTS AND THE REHABILITATION OF THE INFERIOR MEMBERS (Fiep Bulletin - online, 2014)
This bibliographical research of qualitative boarding has objective to characterize the whitewashing of inferior members in the carrying patients of leprosy and its neuropathies. The universal access of the population to the diagnosis, treatment, and the inclusion in the basic actions of health, they aim at its elimination as problem of public health in Brazil. Among the adopted strategies, it is distinguished decentralization of the programmatically actions of leprosy for all the basic net of health of the country. Leprosy is an infectious illness, of chronic evolution that to attack predominantly peripheral nerves e, secondarily, skin and mucosal. The diagnosis is carried through the clinical examination, when one searches dermatological and neurological signals of the illness in more characteristic people who present one or. Correct identification of the degree of the neural problems and the disability of the patient, it is important for the treatment and regular practical orientation of the auto one cares. When penetrating the human organism the etiologic agent mycobacterium leprous, it follows through the sanguineous or lymphatic chain to initiate multiplied in the ganglia, reaching the skin and the sanguineous chain, it reaches the Peripheral Nervous System preferring cells of the system reticulum-endothelial. Contagious and highly infectious illness, not hereditary, of chronic evolution that depends on the specific cellular immunity against the bacillus, slow and treacherous evolution, it has its first clinical manifestation in the spot form that evolves until the gradual of tactile sensitivity and painful loss. The leprosy does not kill, but when is not treated, it is physical cause of incapacities and deformations.
Keywords: leprosy; public health; strategies; peripheral nervous